Efficacy of a Regional Poisoning Treatment Centre in Preventing Further Suicidal Behaviour. Issue 5835 (4th November 1972) - Kennedy, Peter
Abstract : A survey of parasuicide (attempted suicide) in general practice in Edinburgh allowed comparison of the rates of further suicidal behaviour in patients treated for their initial episode in the Edinburgh Regional Poisoning Treatment Centre and in those referred to psychiatrists elsewhere or not referred at all. Further suicidal behaviour was only one-third as common among those treated in the treatment centre as among non-admitted patients; patients referred to other psychiatric services did no better than those who were not referred to a psychiatrist at all. The difference in repetition frequencies could not be accounted for in terms of selection of patients in the treatment centre who were less likely to repeat. The tentative conclusion is made that crisis intervention of the kind available at the Edinburgh centre is effective in secondary prevention. The findings add support to Government recommendations that special units like the one in Edinburgh should be set up in other regions.